4th International Conference of the ICA Commission on the History of Cartography, Budapest, June 28 – 29, 2012 - Marina Rajakovic (Kartografija i Geoinformacije, 2012)
The Commission on the History of Cartography of the International Cartographic Association (ICA) in collaboration with Dr. Zsolt Török from the Loránd Eötvös University in Budapest organized the 4th International Conference of the ICA Commission on the History of Cartography titled Exploration, Discovery, Cartography in Budapest on June 28 and 29, 2012.